Extracellular vesicles derived from human vestibular schwannomas associated with poor hearing damage cochlear cells. Issue 11 (18th May 2016) - Soares, Vitor Y. R.; Atai, Nadia A.; Fujita, Takeshi; Dilwali, Sonam; Sivaraman, Sarada; Landegger, Lukas D.; Hochberg, Fred H.; Oliveira, Carlos A. P. C.; Bahmad, Fayez; Breakefield, Xandra O.; Stankovic, Konstantina M.
Abstract: Background: Vestibular schwannoma (VS) is a tumor of the vestibular nerve that transmits balance information from the inner ear to the brain. Sensorineural hearing loss occurs in 95% of patients with these tumors, but the cause of this loss is not well understood. We posit a role of VS-secreted extracellular vesicles (EVs) as a major contributing factor in cochlear nerve damage. Methods: Using differential centrifugation, we isolated EVs from VS cell line HEI-193 and primary cultured human VS cells from patients with good hearing or poor hearing. The EVs were characterized using a Nanosight device and transmission electron microscopy and by extracting their RNA content. The EVs' effects on cultured murine spiral ganglion cells and organotypic cochlear cultures were studied using a transwell dual-culture system and by direct labeling of EVs with PKH-67 dye. EV-induced changes in cochlear cells were quantified using confocal immunohistochemistry. Transfection of VS cells with a green fluorescent protein–containing plasmid was confirmed with reverse transcription PCR. Results: Human VS cells, from patients with poor hearing, produced EVs that could damage both cultured murine cochlear sensory cells and neurons. In contrast, EVs derived from VS cells from patients with good hearing did not damage the cultured cochlear cells. Conclusions: This is the first report on EVs derived from VSs and on the capacity of EVs from VSs from patients with hearing loss to selectively damage cochlear cells, thereby identifying a potential novel mechanism of VS-associated sensorineural hearing loss.